PENGARUH FINANCIAL LITERACY KONTRIBUSI PEMERINTAH SERTA FINANCIAL RESOURCES TERHADAP KEBERLANGSUNGAN USAHA PADA UMKM DI PASAR SENEN PURWAKARTA - Fitri Fitri; Ali Jamaludin; Rini Rostini (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of Financial Literacy, Government Contribution and Financial Resources on Business Sustainability The sampling technique used is saturated sampling, there are 23 MSME Suppliers in Pasar Senen, Household Industry sub-sector to be sampled. This research is a quantitative study using Multiple Linear Regression to test the hypothesis using SPSS 22. The results of this study indicate that partially there is a positive and significant effect of financial literacy on the business continuity of MSMEs, there is a positive and significant influence of the Government's Contribution to the Business Sustainability of MSMEs. and there is a positive and significant influence of Financial Resources on the Sustainability of MSMEs. And simultaneously Financial Literacy, Government Contribution and Financial Resources have a significant positive effect on the Business Continuity of MSMEs (which are suppliers) in the Purwakarta Senen Market